Doppler volume rendering: a dynamic, piecewise linear spectral representation for visualizing astrophysics simulations - Alghamdi, Reem; Müller, Thomas; Jaspe-Villanueva, Alberto; Hadwiger, Markus; Sadlo, Filip (Computer graphics forum, 2023)
We present a novel approach for rendering volumetric data including the Doppler effect of light. Similar to the acoustic Doppler effect, which is caused by relative motion between a sound emitter and an observer, light waves also experience compression or expansion when emitter and observer exhibit relative motion. We account for this by employing spectral volume rendering in an emission-absorption model, with the volumetric matter moving according to an accompanying vector field, and emitting and attenuating light at wavelengths subject to the Doppler effect. By introducing a novel piecewise linearear representation of the involved light spectra, we achieve accurate volume rendering at interactive frame rates. We compare our technique to rendering with traditional point-based spectral representation, and demonstrate its utility using a simulation of galaxy formation.
Veröffentlicht: 27. Juni 2023
Gesehen am 01.08.2023